2020
DOI: 10.1029/2019gl085112
|View full text |Cite
|
Sign up to set email alerts
|

Competing Topographic Mechanisms for the Summer Indo‐Asian Monsoon

Abstract: The Indo‐Asian Monsoon (IAM) has changed as the topographies of Asia were assembled into their current configuration. Understanding complex interactions between topography and the IAM through time has been hampered, in part, by poorly resolved topography and atmospheric dynamics in climate models. Here, we employ high‐resolution (0.23° × 0.31°) global climate simulations, to more accurately capture these interactions. We find that the Himalayas and Tibet primarily redirect the onshore moisture transport and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 97 publications
(194 reference statements)
3
68
0
Order By: Relevance
“…Boos and Kuang (2013) later reinforced their viewpoint in another co-authored study using high-resolution global Weather Research and Forecast (WRF) model configuration (Ma et al 2014). More recently, using a high-resolution configuration of a GCM, Acosta and Huber (2020) reignited this debate by arguing that topography redirects moisture flow and provides orographic lift, but it does not have a role in the onshore moisture advection. They also suggest that the Iranian Plateau acts as a gatekeeper and its removal allows entrainment of dry air from northwest Asia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boos and Kuang (2013) later reinforced their viewpoint in another co-authored study using high-resolution global Weather Research and Forecast (WRF) model configuration (Ma et al 2014). More recently, using a high-resolution configuration of a GCM, Acosta and Huber (2020) reignited this debate by arguing that topography redirects moisture flow and provides orographic lift, but it does not have a role in the onshore moisture advection. They also suggest that the Iranian Plateau acts as a gatekeeper and its removal allows entrainment of dry air from northwest Asia.…”
Section: Introductionmentioning
confidence: 99%
“…The debate on the role of topography in the development and maintenance of the South Asian Summer Monsoon (hereafter SASM) remains unresolved. It has progressively swayed between the viewpoint that topography acts as an elevated heat source and the viewpoint that it acts as a barrier to prevent thermal exchanges between the cold and dry extratropics and the warm and moist tropics/sub-tropics (e.g., Acosta and Huber 2020, Boos and Kuang 2010, Chakraborty et al 2006, Chen et al 2014, He et al 2018, Li and Yanai 1996, Ma et al 2014, and Wu et al 2012. Interestingly, these strikingly different conclusions are often a result of sensitivity experiments of broadly similar nature.…”
Section: Introductionmentioning
confidence: 99%
“…The two key conditions for generating high biodiversity are complex topographic relief and a dynamic climate ( Spicer, 2017 , and references therein; Rahbeck et al., 2019a ), both of which are found across the Tibetan Region. Recent work has shown that the Asian monsoon, regardless of topography, is a consistent feature arising from the regional land-sea temperature gradient ( Acosta and Huber, 2020 ). Like the biodiversity, the monsoon has a long history, which has shaped both the biota and the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Like the biodiversity, the monsoon has a long history, which has shaped both the biota and the landscape. While regional topographic controls on climate are complex ( Acosta and Huber, 2020 ; Boos and Kuang, 2010 ; Molnar et al., 2010 ), it is not just the topography of the Tibetan Region but paleogeographical constraints further afield that influence monsoon dynamics ( Farnsworth et al., 2019 ). We also now know that models of Tibetan orogeny favoured a few years ago, the most recent of which envisaged the plateau expanding outward from a high Paleogene “Proto Plateau” ( Dai et al., 2012 ; Wang et al., 2014 ), require substantial revision in the light of new fossil discoveries, and that those discoveries are changing radically our knowledge of how Asian biodiversity was generated ( Spicer et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plateau has therefore been envisioned to act as a sensible heat pump. However, because the location of the greatest heating is not over the plateau, but over NW India and eastern Pakistan, the Himalaya are also regarded as having a key orographic influence on the monsoon (Boos and Kuang 2010;Molnar et al 2010), although recent modelling shows that monsoon circulation would exist even in the absence of an orographic barrier (Acosta and Huber 2020).…”
Section: Introductionmentioning
confidence: 99%